Development of E-VIRA (e-module virus integrated reality-augmented): Enhance mental models and problem-solving skills - Zhafira; Hamdiyati, Yanti; Nuraeni, Eni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Based on the analysis, students lack references and in-depth, relevant material content, and still use open printed materials. This results in students' mental models of virus material being unscientific, and their problem-solving skills being low. For this reason, an e-module integrated with Augmented Reality (AR) can be an effective solution. This study aims to develop E-VIRA (E-Module Virus Integrated with Augmented Reality) to improve students' mental models and problem-solving skills. The research method employed is Research and Development (R&D), utilizing the ADDIE stages from inception to development and trial. Data collection instruments include expert validation sheets and cloze tests (for readability). Data analysis techniques are carried out descriptively and quantitatively to calculate the percentage of validity and readability. Participants were selected using purposive sampling, involving grade X high school students. The results showed that E-VIRA was very valid, with a percentage of 97% and 96% from expert validators, and a readability level of 82%. Thus, E-VIRA shows good feasibility and validity. The recommendation of this study is to continue the trial of E-VIRA on a larger scale to measure effectiveness in significantly improving students' mental models and problem-solving skills, as well as explore its application to other abstract biological concepts.